Referring to the Results of International Student Mobility Activities: A Systematic Review and Future Research Agenda and Achievements - Komara, Acep; S., Nelia Fariani (KnE Social Sciences, 2025)
Analytical studies on international student mobility programs are numerous and have grown over the past two decades. However, systematic reviews of such programs and their outcomes have not fully achieved desired output targets. This paper employs a mixed-method approach, combining a systematic literature review with community service (PKM) activities—including seminars, questionnaires, and interviews—to evaluate barriers and motivations for student participation in international mobility programs. Key findings reveal that low English proficiency (e.g., 74.78% of students scored below 400 on TOEFL) and limited institutional support critically hinder engagement, despite high student interest in mobility opportunities. Post-intervention data showed significant improvements in student motivation (93% agreement) and awareness after structured socialization programs. The study identifies gaps in research on student achievement outcomes and proposes a future research agenda to enhance program design, emphasizing intensive language training and institutional collaboration. Recommendations are provided to align management strategies with personal and career benefits for students in a globalized education landscape.